Partisipasi Masyarakat Dalam Pengelolaan Dana Desa Di Desa Watu Galang Kecamatan Mbeliling Kabupaten Manggarai Barat - Yuliana Devita Jemia; David B.W. Pandie; Jim Briand Kolianan (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to find out the Community Participation in Village Fund Management in Watu Galang Village, Mbeliling District, West Manggarai Regency. This research uses a qualitative method with a type of descriptive approach. This research refers to the theory of Community Participation from Cohen and Uphof (1977) which divides community participation into four stages, namely: Community Participation Planning Stage, Implementation Stage, Results Utilization Stage, and Evaluation Stage. The results of the study show that community participation has not been maximized and tends to vary at each stage. At the planning stage, although participatory principles have been implemented, namely by inviting the community to participate in village development plan deliberations, community involvement in this process is still low. At the implementation stage, it shows more active participation, but unevenly. At the stage of utilizing the results, the community has taken advantage of the results of the village fund program in the field of development and empowerment, but public awareness of program maintenance is still minimal. At the evaluation stage, community involvement is still relatively low due to the lack of understanding of the community and the village government has not maximally provided access to the community to actively participate in the evaluation stage